2011
DOI: 10.1097/mpa.0b013e31821fd66a
|View full text |Cite
|
Sign up to set email alerts
|

Improved Quantification of Islet Transplants by Magnetic Resonance Imaging With Resovist

Abstract: Islet transplant survival may be safely and accurately monitored using magnetic resonance imaging with the Resovist. We found in this study that pixel number may correlate more closely than the number of contrast spots with the number of islets transplanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Based on these observations, we may validate the commercial use of SPIONs in clinics based on our experimental results even though a direct comparison may not be available. For clinical labeling of cells in MRI, commercialized SPIONs (Resovist ® , Schering, Germany) have been used at concentrations of 5∼25 ppm (µg/mL) depending on the patient's weight; 43,44 this concentration range is biologically safe based on our data from Figures 2 and 4. seM and TeM observations SEM and TEM images of each cell were obtained after the cytotoxicity test. Figure 5A shows the SEM images of L-929 cells treated with each SPION at a concentration of 500 ppm; the WST-8 assay indicates that the cells might be partly damaged at this concentration.…”
mentioning
confidence: 99%
“…Based on these observations, we may validate the commercial use of SPIONs in clinics based on our experimental results even though a direct comparison may not be available. For clinical labeling of cells in MRI, commercialized SPIONs (Resovist ® , Schering, Germany) have been used at concentrations of 5∼25 ppm (µg/mL) depending on the patient's weight; 43,44 this concentration range is biologically safe based on our data from Figures 2 and 4. seM and TeM observations SEM and TEM images of each cell were obtained after the cytotoxicity test. Figure 5A shows the SEM images of L-929 cells treated with each SPION at a concentration of 500 ppm; the WST-8 assay indicates that the cells might be partly damaged at this concentration.…”
mentioning
confidence: 99%
“…Our results also indicate that MNPs rarely show genotoxicity below at 100 μg/mL, but more careful investigation is required when MNPs are treated at concentrations above 100 μg/mL. For clinical labeling of cells in MRI, commercialized SPIONs (Resovist ® , Schering, Germany) are currently used at concentrations of 5–25 μg/mL depending on the patient’s weight [40,41]; this concentration range is biologically safe based on our data from Figure 2, Figure 3 and Figure 4. Although only dextran-coated SPIONs are approved for human in vivo use by the Food and Drug Administration [42], several SPIONs with various physicochemical properties are in clinical trials and will be utilized for various biomedical applications in the near future [43].…”
Section: Resultsmentioning
confidence: 96%
“…The toxicity of Resovist® for islets was weaker than that of Feridex® in an in vitro assay 54 . The lower toxicity was also confirmed by the Park group 55 . Ris and colleagues also compared three SPIOs, Resovist®, Endorem®, and Feridex®, in terms of their stability and function using rat syngeneic and xenogeneic (human to rat) intraportal transplant models, and found that Resovist® had better insulin-releasing ability and signal stability than Endorem® or Feridex®.…”
Section: Mrimentioning
confidence: 84%